"This is similar to Vincent Chin": Intertextuality, referring expressions, and the discursive construction of Asian American activist identities in an online messaging community. (January 2021) - Nguyen, Naomee-Minh
While the linguistic practices of Asian American Pacific Islander (AAPI) communities have become more widely documented, little is known about how AAPIs discursively create shared political identities, let alone political identities online. In this study, I examine an online messaging community dedicated to AAPI political organizing. Focusing on the discourse of four highly active members of the community, I analyze stance-taking, their uses of what have been called "referring terms" or "referring expressions", and the intertextual references they make. I show how users establish group values through stance-taking and in-group membership through using specific referring expressions, co-constructing the community's identity as a marginalized political group. Through intertextual references, users index shared knowledge of cultural texts regarding AAPI activism and political organizing, such as references to recent and past hate crimes, current news, and AAPI non-profit organizations. I demonstrate how these intertextual references reinforce Becker's notion that social groups' identities lie in a shared collection of "prior texts." Furthermore, I contend that the use of intertextual references aligns the community with the political implications and connotations of the references themselves. Through mutual recognition and understanding of shared texts, members create an online community that transcends ethnic and regional boundaries.